Liver Stiffness by Transient Elastography Correlates With Degree of Portal Hypertension in Common Variable Immunodeficiency Patients With Nodular Regenerative Hyperplasia - DiGiacomo, Daniel V.; Shay, Jessica E.; Crotty, Rory; Yang, Nancy; Bloom, Patricia; Corey, Kathleen; Barmettler, Sara; Farmer, Jocelyn R. (Frontiers in Immunology, 2022)
Nodular regenerative hyperplasia (NRH) is associated with high morbidity and mortality in patients with common variable immunodeficiency (CVID). While liver biopsy is the gold standard for NRH diagnosis, a non-invasive technique could facilitate early disease recognition, monitoring, and/or immune intervention. We performed ultrasound-based transient elastography (TE) in patients with CVID to evaluate liver stiffness and compared this between patients with and without biopsy-proven NRH. Additionally, these data were compared to a cohort followed at our institution for nonalcoholic fatty liver disease (NAFLD), a disease for which TE has routine diagnostic use. Clinical and pathologic features of NRH were evaluated as correlates of liver stiffness and receiver operating characteristic curves were used to define a liver stiffness cut-off with diagnostic utility for NRH among CVID patients. CVID patients with NRH had a more severe disease presentation compared to those without. This included increased autoinflammatory disease co-morbidities, combined B cell and T cell dysfunction, and abnormal liver biochemistries (specifically an increased peak mean alkaline phosphatase level [314 v. 116 U/L, p=0.03]). Results of TE demonstrated a significantly elevated liver stiffness in CVID patients with NRH (mean 13.2 +/- 6.2 kPa) as compared to both CVID patients without NRH (mean 4.9 +/- 0.7 kPa) and non-CVID patients with NAFLD (mean 6.9 +/- 5.5 kPa) (p<0.01). No single or composite histopathologic feature of NRH correlated with liver stiffness including nodule size, nodule density, sinusoidal dilation, fibrosis, and/or lymphocytosis. In contrast, liver stiffness by TE was significantly correlated with clinical parameters of portal hypertension, including an elevated hepatic venous pressure gradient, an increased splenic longitudinal diameter, and presence of varices, peripheral edema, and/or trace ascites. A liver stiffness of greater than 6.2 kPa was a clinically significant cut-off for NRH in CVID patients. We propose that transient elastography has diagnostic utility in CVID, particularly in the presence of immunophenotypic features such as combined B cell and T cell dysfunction, autoinflammatory co-morbidities, and/or abnormal liver tests. Elevated liver stiffness by TE should raise suspicion for NRH in patients with CVID and prompt expedited evaluation by hepatology.